2007
DOI: 10.1111/j.1600-0846.2007.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between ultrasonography (Dermascan C version 3) and transparency profilometry (Skin Visiometer SV600)

Abstract: Therefore, the ultrasonography system may be considered a very useful method in wrinkle evaluation with the transparency profilometry. However, further study will be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
1
19
0
3
Order By: Relevance
“…In concordance with the data previously published [16] in the present study, the young group showed higher dermal density than the old group, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In concordance with the data previously published [16] in the present study, the young group showed higher dermal density than the old group, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…The mechanical properties of skin are influenced by many factors. They are known to be determined mainly by the three‐dimensional structure that consists of the extracellular matrix and the collagen and elastic fibres and are affected by the thickness of the epidermis or the entire skin and the degree of epidermal hydration [16, 17]. In our study, elasticity (R2, R5) and recovery rate (R7, R8) tended to decrease.…”
Section: Discussionmentioning
confidence: 50%
“…Earlier investigations have shown that the echogenic density of ultrasound is high, based on the quantity of collagen and density of dermal collagen [21,23,24]. The evaluation of echogenicity using Dermascan C â has also been used in previous studies [19,20,23,[25][26][27]. The echogenicity of the upper and lower dermis has also been used for the evaluation of papillary and reticular layer of dermis in a previous study [28].…”
Section: Image Analysismentioning
confidence: 99%
“…The majority of these tools use a silicone replica of the skin, after which the topography of the replica is measured. This indirect measurement is performed by use of mechanical, 14 optical, 15 laser, 16 transparency, 17,18 or interference fringe projection profilometry. 19 The use of replicas is time-consuming and, therefore, not feasible in an outpatient setting.…”
mentioning
confidence: 99%